UNDERSTANDING THE RAPIST, RAPE VICTIMS AND THE LAW OF RAPE (NATIONAL CAPITAL LAW JOURNAL, 1997)
NA
Keywords: Rape Law; Sexual Violence Against Women; Rape Victims; Criminal Justice System; Child Sexual Abuse; Custodial Rape; Gender Bias; Victim Compensation; Women's Dignity; Sentencing Policy.